2006
DOI: 10.1136/pgmj.2005.037515
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular complications of severe acute respiratory syndrome

Abstract: Background and Aims: Severe acute respiratory syndrome (SARS) is a virulent viral infection that affects a number of organs and systems. This study examined if SARS may result in cardiovascular complications. Methods and Results: 121 patients (37.5 (SD13.2) years, 36% male) diagnosed to have SARS were assessed continuously for blood pressure, pulse, and temperature during their stay in hopsital. Hypotension occurred in 61 (50.4%) patients in hospital, and was found in 28.1%, 21.5%, and 14.8% of patients during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
276
0
16

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 315 publications
(308 citation statements)
references
References 19 publications
16
276
0
16
Order By: Relevance
“…Previous studies have confirmed that the immune abnormality is related to the pathogenesis of SARS-CoV infection 45 .…”
Section: Cytokine Storm and Inflammationmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous studies have confirmed that the immune abnormality is related to the pathogenesis of SARS-CoV infection 45 .…”
Section: Cytokine Storm and Inflammationmentioning
confidence: 78%
“…ACE2-dependent manner 45 . The trimers of the SARS-CoV spike protein initially extends into a hydrophobic pocket of ACE2 catalytic domain 46 , which consequentially leads to the endocytosis of SARS-CoV particles and fusion of virus to cardiomyocytes with the help of type II transmembrane serine proteases (TMPRSS2) 47 , finally downregulating ACE2 expression in cardiomyocytes 48,49 .…”
Section: Sars-cov Have Been Previously Demonstrated To Induce Myocardmentioning
confidence: 99%
“…Losartan, telmisartan, olmesartan (and additional AT1R antagonists) are widely applied in the clinic since the 1990s for control of hypertension and kidney disorders, and are known as safe drugs that are rarely implicated in adverse drugs events (Deppe, Böger, Weiss, & Benndorf, 2010;McIntyre, Caffe, Michalak, & Reid, 1997). However, it should be noted that around half of SARS-CoV patients developed hypotension during their hospitalization (Yu et al, 2006). At time of writing this commentary, no comprehensive information is available on hypotension rates among hospitalized SARS-CoV-2 patients; it is thus premature to estimate what percentage of SARS patients of the currently ongoing epidemic can be safely treated with AT1R blockers without risking exacerbated hypotension.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Transient atrial fibrillation was seen in 1 patient. 95 ARF ARF occurred in 17% of patients admitted with probable SARS. 96 Most of the patients were men (77%), older, and more often had underlying illnesses (diabetes: 38% vs 6%, P<.01; and, heart failure: 38% vs 2%, P<.001).…”
Section: Cardiovascular Complicationsmentioning
confidence: 99%